Metabolic Profiling of Diabetic Cats in Remission - Gottlieb, Susan; Rand, Jacquie; Anderson, Stephen T.; Morton, John Murray; Dias, Daniel A.; Boughton, Berin A.; Roessner, Ute; Ramadan, Ziad (Frontiers in Veterinary Science, 2020)
Background: The majority of diabetic cats in remission have abnormal glucose tolerance and an improved understanding of metabolism is necessary to identify metabolic markers of prediabetes. Objectives: Using a metabolomics approach, identify and compare differences in plasma metabolites between diabetic cats in remission and healthy control cats. Secondly, assess whether identified metabolites are predictors of diabetic relapse. Animals: Twenty cats in diabetic remission for a median of 101 days, and 22 healthy matched control cats. Methods: Cats were admitted to a clinic, and casual blood glucose was recorded. After a 24 hour fast, blood glucose concentration was measured, then a blood sample taken for metabolomic (GCMS and LCMS) analyses. Three hours later a simplified intravenous glucose tolerance test (1g glucose/kg) was performed. Cats were monitored for diabetes relapse for at least 9 months (270 days) after baseline testing. Results: 16 metabolites were identified that differed (p≤ 0.05) between remission and control cats: 10 amino acids, stearic acid, and urea (all lower in remission cats), and glucose, glycine, xylitol, urea, and carnitine (all greater in remission cats). Moderate correlations were found between identified metabolites and glycemic responses in this cohort of cats in remission, which continued to display impaired glucose tolerance and mildly impaired fasting glucose. No metabolite was identified as a predictor of relapse. Conclusion and clinical importance: This study shows that cats in diabetic remission have abnormal metabolism. Metabolites identified are potential markers of prediabetes and may inform future therapies to improve glucose tolerance in diabetic cats.